Nosocomial Infection: General Principles and the Consequences, Importance of its Control and an Outline of the Control Policy - A Review Article (Bangladesh Medical Journal, 2009)
Nosocomial Infections or more commonly known as Hospital Acquired Infection [HAI], in short , may be defined as "Any infection that is being acquired in a hospital, particularly when the source or the risk factor for it is one peculiar to the hospital". The matter of concern is that nosocomial infection or hospital acquired infection at the moment affect not less than 400,000 hospitalized patients at anytime in the world and are direct or contributory causes of death of more than 80,000 cases a year in the U.S.A. alone. Billions of dollars are used annually in the developed countries alone for the control of just these hospital acquired infections alone which reflect another aspect of the magnitude of the problem. The magnitude of the problems of the nosocomial infections in other countries is even more serious and in a developing country like Bangladesh, one could one assume (since there is no established recognized statistics) the pathetic picture in terms of morbidity, mortality as well as the invisible but very valuable economic loss.The other frustrating fact regarding the natural history of Nosocomial or Hospital Acquired Infections is that they can not be eradicated entirely; but many of them can be prevented by proper control measures. In places where control programmes can be implemented, there had been a proven reduction of morbidity and mortality. Furthermore, the money that can be saved by reduction of nosocomial infections is much more used for infection control.   DOI: 10.3329/bmj.v38i2.3576 Bangladesh Medical Journal 38(2) 2009 60-64